2005
DOI: 10.1029/2004gl021269
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a long‐term decrease in thermospheric neutral density

Abstract: [1] Long-term thermospheric neutral density trends near 400 km altitude are analyzed using high accuracy satellite drag measurements over the common time period 1970 -2000. Data coverage is over all latitudes and local times and an extensive range of solar and geomagnetic conditions. Densities are compared to empirical models that remove known variations related to solar activity, latitude, local time, day of year and altitude. An average unmodeled secular neutral density decrease of 1.7% per decade is detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 15 publications
12
105
0
Order By: Relevance
“…This long-term decreasing trend of neutral density has been observed using long-term satellite drag data (e.g., Keating et al 2000;Emmert et al 2004Emmert et al , 2008Marcos et al 2005). The estimated density trend at 400 km ranges from −1.7%/decade to −3.0%/decade, for the past 3 to 4 decades.…”
Section: Long-term Trendsmentioning
confidence: 51%
“…This long-term decreasing trend of neutral density has been observed using long-term satellite drag data (e.g., Keating et al 2000;Emmert et al 2004Emmert et al , 2008Marcos et al 2005). The estimated density trend at 400 km ranges from −1.7%/decade to −3.0%/decade, for the past 3 to 4 decades.…”
Section: Long-term Trendsmentioning
confidence: 51%
“…[21] Global mean trends in thermospheric mass density r have been studied from satellite drag data over the last few decades [Keating et al, 2000;Emmert et al, 2004Emmert et al, , 2008Marcos et al, 2005]. At 400 km the relative trends range from about dr/r = À5% decade À1 at low solar activity [Keating et al, 2000;Emmert et al, 2008] to À2% decade À1 at high activity [Emmert et al, 2004[Emmert et al, , 2008 with average values ranging between À1.7 and À2.7% decade À1 [Marcos et al, 2005;Emmert et al, 2008].…”
Section: Trend Magnitudementioning
confidence: 99%
“…[4] As well as short-term, storm-driven changes in the thermosphere, satellite studies at middle latitudes have shown that the global thermosphere is gradually contracting [Keating et al, 2000;Marcos et al, 2005;Emmert et al, 2008]. The rate of decrease in density at 400 km has been estimated to range from 2% to 5% per decade at solar maximum and minimum, respectively [Emmert et al, 2004[Emmert et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%